CHALLENGES AND EDUCATIONAL PATH OF A STUDENT WITH HIGH SKILLS/INTELECTUAL GIFTEDNESS - Mendonca, Michelle Maia; Tescaro S Lino, Carla Cristine [UNESP]; Munhoz, Diogo Janes (Univ Metodista Piracicaba-unimep, 2021)
This is a case study on the need to identify and make curricular flexible for students who have characteristics of High Skills/Intelectual Giftedness. The student participating in this research resides and studies in a city located in the interior of the state of Parana, and was identified as Bob, to preserve his identity. Analyzing the pedagogical work with the student and whether the teachers were prepared to identify students with Intelectual Giftedness in the classroom, became the problem of this research. The objective, therefore, was to present the challenges of a 12-year-old student with High Skills/Intelectual Giftedness in the intellectual and academic areas during his school trajectory, from Early Childhood Education to the 8th year of Elementary School II, including the period of remote education needed in the year 2020. It was also considered their late Intelectual Giftedness identification and the challenges faced in the schools where he studied. It was concluded that the literature, according to authors such as Renzulli, Virgolim, Sabatella and Delou, among others, shows in their research that few students with such skills have been properly identified in public and private schools, after all, most education professionals do not recognize the special needs of these students and do not understand that the area of High Skills/Intelectual Giftedness, loaded with myths and decontextualized information, is inserted in the context of Special Education.
Keywords: SPECIAL EDUCATION; SCHOOLING; EDUCATIONAL INCLUSION; GIFTEDNESS STUDENT